Comparative effects of aluminum and ouabain on synaptosomal choline uptake, acetylcholine release and (Na+/K+)ATPase - Silva, Virgilia S.
Closing the gap between adverse health effects of aluminum and its mechanisms of action still represents a huge challenge. Cholinergic dysfunction has been implicated in neuronal injury induced by aluminum. Previously reported data also indicate that in vivo and in vitro exposure to aluminum inhibits the mammalian (Na+/K+)ATPase, an ubiquitous plasma membrane pump. This study was undertaken with the specific aim of determining whether in vitro exposure to AlCl3 and ouabain, the foremost utilized selective inhibitor of (Na+/K+)ATPase, induce similar functional modifications of cholinergic presynaptic nerve terminals, by comparing their effects on choline uptake, acetylcholine release and (Na+/K+)ATPase activity, on subcellular fractions enriched in synaptic nerve endings isolated from rat brain, cuttlefish optic lobe and torpedo electric organ. Results obtained show that choline uptake by rat synaptosomes was inhibited by submillimolar AlCl3, whereas the amount of choline taken up by synaptosomes isolated from cuttlefish and torpedo remained unchanged. Conversely, choline uptake was reduced by ouabain to a large extent in all synaptosomal preparations analyzed. In contrast to ouabain, which modified the K+ depolarization evoked release of acetylcholine by rat, cuttlefish and torpedo synaptosomal fractions, AlCl3 induced reduction of stimulated acetylcholine release was only observed when rat synaptosomes were challenged. Finally, it was observed that the aluminum effect on cuttlefish and torpedo synaptosomal (Na+/K+)ATPase activity was slight when compared to its inhibitory action on mammalian (Na+/K+)ATPase. In conclusion, inhibition of (Na+/K+)ATPase by AlCl3 and ouabain jeopardized the high-affinity (Na+-dependent, hemicholinium-3 sensitive) uptake of choline and the Ca2+-dependent, K+ depolarization evoked release of acetylcholine by rat, cuttlefish and torpedo synaptosomal fractions. The effects of submillimolar AlCl3 On choline uptake and acetylcholine release only resembled those of ouabain when rat synaptosomes were assayed. Therefore, important differences were found between the species regarding the cholinotoxic action of aluminum. The variability of (Na+/K+)ATPase sensitivity to aluminum of cholinergic neurons might contribute to their differential susceptibility to this neurotoxic agent. (C) 2007 Elsevier Ireland Ltd. All rights reserved.